Activation analysis of human hair as a tool for environmental pollution monitoring - Obrusník, I (Journal of hygiene, epidemiology, microbiology, and immunology, 1986)
Recent development and uses of neutron activation techniques for human hair analyses are reviewed. The method of neutron activation analysis (NAA) appears to have the potential to be used as a tool for environmental pollution monitoring. Principally, two types of NAA procedure are in use nowadays for multielement analyses of human scalp hair. The more common of these is the method of instrumental neutron activation analysis (INAA), consisting of a single short-term (3-10 hours) exposure of hair to a beam of neutrons in a nuclear reactor, followed by two measurements of gamma-ray spectra at 2-3 days and 3-4 weeks after the end of irradiation. The following microelements can be commonly determined by this type of activation procedure: As, Au, Br, Cu, K, La, Na, Sb, Sm, Co, Cr, Cs, Fe, Hg, Rb, Sc, Se and Zn. The other of the two procedures involves the use of radiochemical separation techniques and is employed for quantitative determinations of elements that are not easily determined by INAA (Mo, Cd, Ni, etc.), or in cases where there is a need to achieve the lowest possible limits of analytical determination. The accuracy of NAA techniques is strongly dependent on the hair sampling and hair sample processing methods used. The analytical error of this method may vary within the range of 5-15%. Its applicability as a tool for monitoring the environmental pollution level is here demonstrated on an example of groups of individuals living in the areas differing by the degree of environmental pollution. The use of other biopsy materials, such as e.g. mammalian hair, for the purpose of environmental exposure monitoring is also considered in this review.
Keywords: Environmental Monitoring; radiochemie; Activation Analysis; stopové prvky; Air Pollutants; Radiochemistry; monitorování životního prostředí; spektrometrie gama; Spectrometry, Gamma; odběr biologického vzorku; vlasy, chlupy; Neutron Activation Analysis; neutronová aktivační analýza; aktivační analýza; látky znečišťující vzduch; lidé; Humans; Specimen Handling; Trace Elements; Hair